The shape of landscape: An experimental research to the perception of the concept of landscape - Hokwerda, Renno (Student Undergraduate Research E-journal!, 2015)
Landscape is constructed socially by means of communication and utilisation, but the underlying processes of these remain poorly understood. After a theoretical discussion, an experimental empirical study was conducted using the mental mapping technique. Mental maps reflect how individuals perceive the concept of landscape, and using a hybrid qualitative and quantitative analysis, it was extracted how individuals’ choices can be placed within a macro-societal framework. The conclusions read that indeed landscape is constructed partly through individual utilisation, but that communicating place and landscape is of more importance. The mental mapping technique proved valuable but difficult to operationalise.